2021
DOI: 10.1016/j.eclinm.2020.100688
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 risk, disparities and outcomes in patients with chronic liver disease in the United States

Abstract: Background: Scientific evidence is lacking regarding the risk of patients with chronic liver disease (CLD) for COVID-19, and how these risks are affected by age, gender and race. Methods: We performed a case-control study of electronic health records of 62.2 million patients (age >18 years) in the US up to October 1st, 2020, including 1,034,270 patients with CLD, 16,530 with COVID-19, and 820 with both COVID-19 and CLD. We assessed the risk, disparities, and outcomes of COVID-19 in patients with six major CLDs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 26 publications
(33 reference statements)
1
50
1
Order By: Relevance
“…The findings are consistent with studies that demonstrate an association between CLD and poor COVID-19 outcomes. 7 , 8 , 9 However, the results are in contrast to a recent multi-institutional study that found an association between Latino ethnicity and severe COVID-19 disease among patients with decompensated cirrhosis, but no association between Latino ethnicity and COVID-19–related mortality. 7 …”
contrasting
confidence: 89%
“…The findings are consistent with studies that demonstrate an association between CLD and poor COVID-19 outcomes. 7 , 8 , 9 However, the results are in contrast to a recent multi-institutional study that found an association between Latino ethnicity and severe COVID-19 disease among patients with decompensated cirrhosis, but no association between Latino ethnicity and COVID-19–related mortality. 7 …”
contrasting
confidence: 89%
“…There is very limited data on hepatitis C virus (HCV) and COVID-19. Wang et al , 52 in their case-control study of over 1 million patients with cirrhosis, included 16,530 with COVID-19 and 820 with COVID-19 and chronic liver disease (CLD) and reported higher odds for patients with HCV in acquiring COVID-19 than for those without [adjusted odds ratio of 12.9]. Thus, although these findings would support the notion that patients with HCV-related CLD are at a greater risk for acquiring COVID-19 infections, there is a dearth of data to validate this finding or identify the impact of COVID-19 on disease course, management and outcome.…”
Section: Liver Manifestations Of Covid-19mentioning
confidence: 99%
“…Accordingly, several predictive models that seek to optimize hospital resource management and clinical decisions have been developed (Jehi et al, 2020a;Jehi et al, 2020b;Gong et al, 2020;Liang et al, 2020;Wynants et al, 2020;Zhao et al, 2020). To a large degree, these informatic tools leverage the vast and rich health information available from Electronic Health Record (EHR) data (Jehi et al, 2020b;Oetjens et al, 2020;Osborne et al, 2020;Vaid et al, 2020;Wang et al, 2021a;Wang et al, 2021b;Estiri et al, 2021;Halalau et al, 2021;Schwab et al, 2021). EHR systems contain longitudinal data about patients' demographics, health history, current and past medications, hospital admissions, procedures, current and past symptoms and conditions.…”
Section: Introductionmentioning
confidence: 99%